Benefits and limitations of electrocardiographic and echocardiographic screening in top level endurance athletes - A. Jakubiak, Agnieszka; Konopka, Marcin; Bursa, Dominik; Król, Wojciech; Anioł-Strzyżewska, Krystyna; Burkhard-Jagodzińska, Krystyna; Sitkowski, Dariusz; Kuch, Marek; Braksator, Wojciech (Biology of Sport, 2021)
The study was designed to assess the usefulness of routine electrocardiography (ECG) as well as transthoracic echocardiography (TTE) in screening top level endurance athletes. An additional goal was to attempt to identify factors determining occurrence of adaptive and abnormal changes in ECG and TTE. The retrospective analysis included basic medical data, ECG and TTE results of 262 athletes (123 rowers, 32 canoeists and 107 cyclists), members of the Polish National Team. The athletes were divided into two age groups: young (≤ 18 years; n = 177) and elite (> 18 years; n = 85). ECG and TTE measurements were analysed according to the International Recommendations from 2017 and 2015, respectively. Adaptive ECG changes were found in 165 (63%) athletes. Abnormal ECG changes were identified in 10 (3.8%) athletes. 98% of athletes exceeded TTE norms for the general population and 26% exceeded norms for athletes. The occurrence of both adaptive ECG findings and abnormalities in the TTE (in norms for athletes) was strongly associated with the years of training, hours of training per week and the age of the athlete. Male gender and the years of training were independent predictors of the ECG and TTE findings. Abnormal ECG changes were not related to the time of sport. Among 10 athletes with ECG changes, only 3 had changes in TTE and no relationship was found between abnormal finding in ECG and TTE (p = 0.45). ECG and TTE screening complement each other in identifying endurance athletes requiring treatment or verification. Unlike abnormal ECG changes, adaptive ECG changes and TTE abnormalities are strongly related to the training duration, which reflects physiological adaptation of the heart to physical exertion in high endurance athletes.